Effects of Homogenization on Organoleptic Quality and Stability of Pasteurized Milk Samples - Yiwei Shao; Yiting Yuan; Yanmei Xi; Tong Zhao; Nasi Ai (Agriculture, 2023)
The organoleptic quality and stability of pasteurized milk are closely related to consumption choices. Our study investigated the effects of different homogenization pressures on the organoleptic quality and stability of pasteurized milk during shelf life. The three homogenization pressures used in this work were 0, 150, and 300 bar. The three homogenization times were 40 s, 56 s, and 60 s respectively. The sensory quality and stability of pasteurized milk after storage for 8, 72, and 168 h were investigated by sensory description experiment, electronic nose technology, and physical properties (such as stability, color, and particle size). The results showed that, at the same storage time, different homogenization pressures had prominent effects on the creamy, milk, fat, and fresh milk flavors of pasteurized milk, together with different effects on the stability of pasteurized milk. The pasteurized milk samples stored for 8 h under the three homogenization pressures had a good fresh milk flavor, and its strong fat flavor affected the taste. The pasteurized milk samples stored for 72 h under 150-bar homogenization pressure had uniform texture, excellent milk flavor, and delicious taste, and the stability of milk reached the best state. Pasteurized milk samples stored for 168 h under three homogenization pressures had increased metallic, sour, and salty tastes in varying degrees, affecting the flavor quality and stability of milk. In short, the organoleptic quality and stability of pasteurized milk samples stored for 72 h under 150-bar homogenization pressure (ML72) were the most optimal. The results provide a scientific theoretical basis for improving product organoleptic quality and stability, which may inspire a new production strategy to innovate pasteurized milk product. This study examined the impact of different homogenization pressures (0, 150, and 300 bar) on the organoleptic quality and stability of pasteurized milk during shelf life (8, 72, and 168 h).